MODEL PEMBELAJARAN PROBLEM BASED LEARNING FISIKA SEBAGAI IMPLEMENTASI KURIKULUM MERDEKA - Cyrilla, Shafa Rahma; Fitriyani, Vivi; Jati Ningsih, Siska Miati; Bayyinah; Febriani, Immanuella Senja Dwi; Muflih, Abdullah Mu’adz; Jamaludin, Jaja; Heriyanto, Yayat W.; Luhukay, Jack Roland; Djatmiko, Wisnu; Yaqin, Achmad Ainul; Sugihartono, Iwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Problem-Based Learning (PBL) is a teaching model that emphasizes real-world problem-solving as the focal point of learning. In the context of the Merdeka Curriculum, this approach enables students to take an active role in their learning. This article reports on the responses of teachers from Jakarta Islamic School Pondok Karya Pembangunan (JIS-PKP) Senior High School to a seminar titled